Public health impact of nirsevimab against acute lower respiratory infections associated with respiratory syncytial virus among Chinese infants: a modelling study - Xiaozhen Lai; Yidi Ma; Weishun Zou; Samira Soudani; Hai Fang (Expert Review of Vaccines)
Background Respiratory syncytial virus (RSV) causes substantial acute lower respiratory infections (ALRI), particularly during infants’ first RSV season. This study evaluated the impact of a new long-acting monoclonal antibody, nirsevimab, on Chinese infants.Research design and methods A monthly decision-analytic model assessed nirsevimab’s impact for the 2024 birth cohort, incorporating domestic RSV-ALRI parameters. Outcomes included RSV-ALRI cases, hospitalization involving intensive care unit admission and mechanical ventilators use, in-hospital deaths and quality-adjusted life years (QALYs).Results Without intervention, a total of 873 035 RSV-ALRI cases (269 067 hospitalized), 2 125 deaths, 74 422 QALY loss and $998 million costs were estimated, where higher-risk infants (5.23% of the cohort) accounted for 8.83% of inpatient cases, 12.23% of deaths and 9.87% of costs. With 20% coverage for higher-risk and 10% for healthy term infants, nirsevimab could prevent 61 094 RSV-ALRI cases (19 905 hospitalized), 168 deaths and 5 808 QALY loss, saving $77 million. Tripling the coverage could avert 183 282 RSV-ALRI cases (59 713 hospitalized), 506 deaths and 17 425 QALY loss, saving $231 million.Conclusions Nirsevimab introduction could effectively mitigate RSV-ALRI burden in Chinese infants, and enhanced coverage is recommended to maximize the public health benefits.